2016
DOI: 10.1007/s10195-016-0396-9
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of transpedicular screw fixation of the subaxial cervical spine in the Arab population: a computed tomography-based morphometric study

Abstract: BackgroundTranspedicular screw fixation of the cervical spine provides excellent biomechanical stability. The feasibility of inserting a 3.5-mm screw in the pedicle requires a minimum pedicle diameter of 4.5 mm. This diameter allows at least 0.5 mm bony bridge medially and laterally in order to avoid pedicle violation which can result in neurovascular complications. We aim to evaluate the feasibility of this technique in Arab people since no data are available about this population.Materials and methodsThis cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…Pedicle endosteal width in this study was the smallest parameter of all parameters, and it continuously increased from C3 to C7, and this was in keeping with previous studies [ 4 , 13 , 14 ]. The pedicle width of the Ugandan population studied is smaller than that reported in studies elsewhere among Europeans and Americans as reported a systematic review study (Liu, Napolitano, & Ebraheim, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…Pedicle endosteal width in this study was the smallest parameter of all parameters, and it continuously increased from C3 to C7, and this was in keeping with previous studies [ 4 , 13 , 14 ]. The pedicle width of the Ugandan population studied is smaller than that reported in studies elsewhere among Europeans and Americans as reported a systematic review study (Liu, Napolitano, & Ebraheim, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…Pedicle endosteal width in this study was the smallest parameter of all parameters and it continuously increased from C3 to C7 and this was in keeping with previous studies (3,16,17). The pedicle width of the Ugandan population studied is smaller than that reported in studies elsewhere among Europeans and Americans as reported a systematic review study (18).…”
Section: Pedicle Endosteal /Inner Widthsupporting
confidence: 90%
“…In comparison, Rao et al 12 noted the overall mean PAL to be 32.6 mm at C3, 32 mm at C4, 32.55 mm at C5, 32.35 mm at C6, and 30.75 mm at C7 in the American population. Al-saeed et al 30 noted in an Arab population that PAL was 32.2 mm at C3, 32.3 mm at C4, 33 mm at C5, 33.5 mm at C6, and 34 mm at C7. Wasinpongwanich et al 23 noted in the Thai population that PAL was 29.10 mm at C3, 30.48 mm at C4, 32.05 mm at C5, 33.40 mm at C6, and 34.36 mm at C7.…”
Section: Discussionmentioning
confidence: 98%